2015
DOI: 10.1021/acsphotonics.5b00244
|View full text |Cite
|
Sign up to set email alerts
|

Optically Monitored Electrical Switching in VO2

Abstract: We demonstrate a hybrid silicon-vanadium dioxide (Si-VO 2 ) electro-optic modulator that enables direct probing of both the electrically triggered semiconductor-to-metal phase transition in VO 2 and the reverse transition from metal to semiconductor. By using a twoterminal in-plane VO 2 electrical switch atop a single-mode silicon waveguide, the phase change can be initiated electrically and probed optically, separating the excitation and measurement processes and simplifying the analysis of the metal-to-semic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(127 citation statements)
references
References 48 publications
2
125
0
Order By: Relevance
“…Another mechanism triggering the electrical‐stimulated MIT in VO 2 is Joule heating or electrothermal mechanism by locally melting the insulators as current passing through VO 2 . This phenomenon was recently confirmed by optically monitoring the MIT process in two‐terminal in‐plane VO 2 electrical switching that stacking on single‐mode silicon waveguide, and they found the filamentary behavior induced by joule heat instead of the electrons injection is the main reason to induce the electrical‐stimulated MIT . Cavalleri et al found that the formation of the rutile unit cell was essential for the metallic behavior of VO 2 , even when the correlated d band was highly depleted (holes injection), and confirmed that the dominant mechanism of MIT was thermal triggering through ultrafast spectroscopy …”
Section: Electrically Stimulated Devicesmentioning
confidence: 92%
See 1 more Smart Citation
“…Another mechanism triggering the electrical‐stimulated MIT in VO 2 is Joule heating or electrothermal mechanism by locally melting the insulators as current passing through VO 2 . This phenomenon was recently confirmed by optically monitoring the MIT process in two‐terminal in‐plane VO 2 electrical switching that stacking on single‐mode silicon waveguide, and they found the filamentary behavior induced by joule heat instead of the electrons injection is the main reason to induce the electrical‐stimulated MIT . Cavalleri et al found that the formation of the rutile unit cell was essential for the metallic behavior of VO 2 , even when the correlated d band was highly depleted (holes injection), and confirmed that the dominant mechanism of MIT was thermal triggering through ultrafast spectroscopy …”
Section: Electrically Stimulated Devicesmentioning
confidence: 92%
“…For example, the thermally induced MIT has been extensively studied for electro/thermal‐chromic, actuators, and thermoelectricity applications, while electrical field manipulation can be used for memory devices and Mott field effect transistor (FET) to circumvent the fundamental limits encountered in Si‐based electronics . It has been shown that VO 2 based photodetectors can respond to optical stimulation over a broad spectral range from terahertz to ultraviolet (UV), and the time‐resolved optical pump‐probe techniques provide an effective means to study the phase transition dynamics in VO 2 . The MIT of VO 2 initiated by the electrochemical reaction shows potential in electrochromic device …”
Section: Introductionmentioning
confidence: 99%
“…For instance, even in the electrical realization (as shown here) of large coupled oscillatory systems, one of the major challenges is to be able to measure simultaneously, speedily, and accurately the phase of the oscillators as the phase dynamics form the fundamental basis of the computational primitive using coupled oscillators. An optical phase read-out scheme can potentially be designed for the oscillators, as the VO 2 -based phase transition devices show a significant change in optical response across the phase transition; the optical transmission dramatically reduces as VO 2 undergoes IMT [33]. Further, optically tuned VO 2 has been shown as a memory capacitance and thus can be potentially incorporated as a tunable coupling element in the coupled oscillator system.…”
Section: Coupling Imt Oscillators: Electrical and Opticalmentioning
confidence: 99%
“…[16] Here, we continue to push the performance of the hybrid Si-VO 2 electrooptic modulator system with VO 2 integrated onto a Si ring resonator. In addition to demonstrating the potential for the Si-VO 2 hybrid system as a competitive low power, high speed, and compact modulator, our work provides additional insight into the dynamics of the SMT of VO 2 .…”
Section: Introductionmentioning
confidence: 98%